The role of digitalisation in supporting farmers and strategic policies for food security and sustainability in Europe: A review - Giri Prasad, Kandel; Polakova, Jana; Hamouz, Pavel; Hruska, Adam; Varvaris, Ioannis; Manikas, Ioannis (My University, 2026)
Ensuring food security while reducing dependency on agrochemical inputs has become a strategic priority for European agriculture amid climate change, geopolitical instability and environmental degradation. This paper examines the role of digitalisation in supporting sustainable and resilient agri-food systems across the European Union. Drawing upon an extensive literature review, we analyse the current state of agricultural digitalisation, the systematic barriers constraining its uptake, and the effectiveness of key EU policy instruments, mainly the Common Agricultural Policy. Our study shows that several digital technologies, such as precision agriculture, sensor-based monitoring, and decision-support systems that have reached high technological readiness levels, yet adoption remains uneven. In terms of precision agriculture, several technologies exist, including the variable rate technology for crops that can increase wheat production by 1% to 10%, offering savings in nitrogen fertilisation ranging from 4% to 37%. However, there are trade-offs to consider, such as power asymmetries, rebound effects, and a digital divide stemming from uneven digital literacy among farmers. The paper explores three detailed implementation pathways, including mechanisms, resources, feasibility and time horizon. The pathways include 1) EU framework for agrochemical independence and agricultural data digitalisation; 2) CAP Eco-schemes for low-input digitalisation; and 3) Cooperative digital inclusion for small and medium farms. Overall, the findings underscore that only digitalisation is not a panacea, but its contribution to food security depends on governance, inclusive policy design and long-term investment in enabling conditions.
Keywords: Digital solutions; Agrochemical independence; One-stop-shop; Common agricultural policy; Precision agriculture; EU strategies